ANALISIS REKONSILIASI FISKAL ATAS LAPORAN KEUANGAN KOMERSIAL TERHADAP PPH PADA PT. DHARMA Tbk - Annisa Septia Kurniadewi; Nurita Manurung; Ruth Oktafiana Sitompul; Fitri Salsabyla (Jurnal Ilmiah Akuntansi, 2026)
The research examines the execution of financial alignment in assessing the corporate income tax owed at PT. Dharma Tbk for the 2022 fiscal year. Fiscal reconciliation is required due to discrepancies in the evaluation of gains and expenses among the Financial Accounting Standards (SAK) and prevailing tax regulations, which give rise to permanent and temporary differences that affect taxable income. Using a qualitative descriptive approach along with case studies, this analysis explores commercial financial statements, fiscal reconciliation reports, and relevant financial documentation issued by the company. The findings indicate that the firm has prepared its commercial financial statements in line with SAK and has appropriately recognized tax implications, including tax benefits and obligations. The fiscal reconciliation process conducted by the company includes a negative correction to interest income subject to final income tax and a positive correction to depreciation expenses arising from differences in useful life based on tax legislation. Following these adjustments, fiscal profit increased from Rp. 29.768.019.322 to Rp. 29.619.951.643, resulting in a corporate income tax liability of Rp. 7.404.987.911. Overall, this study underscores the essential role of fiscal reconciliation in ensuring tax compliance, enhancing the accuracy of taxable income determination, and supporting transparent financial reporting for corporate taxpayers.